The radiolarian fauna during the Younger Dryas–Holocene transition in Andfjorden, northern Norway - Kjell R. Bjørklund; Svetlana B. Kruglikova; Øyvind Hammer (Polar Research, 2019)
We report on the changing radiolarian faunas from the Younger Dryas (ca.12.9 calibrated thousands of years BP [cal. Ky BP]) and into the Holocene (ca. 10.3 cal. Ky BP) in the core JM99-1200 from Andfjorden, northern Norway. Temperature reconstructions using both the Q-mode factor analysis and modern analogue technique methods show stable, cold temperatures below ca. 410 cm core depth, followed by abrupt warming into a relatively stable Holocene temperature regime. Age-depth modelling with three different methods gives an age of ca. 11.9–12.0 cal. Ky BP at this core depth, clearly older than the Younger Dryas–Holocene transition at ca. 11.65 cal. Ky BP according to ice core chronology. Considering that the age models may be insufficiently informed in an interval without radiometric dates, it is possible that the base of the Holocene is indeed at 410 cm, as indicated by the radiolarian and other core data. Such a change in the chronology would have implications for previously published work on the JM99-1200 core. Alternatively, the abrupt warming in Andfjorden predated the Younger Dryas–Holocene transition by a few hundred years. A distinct cold pulse at ca. 315–335 cm, or 11.4–11.5 cal. Ky BP is interpreted as the Preboreal Oscillation. The Preboreal Oscillation has not previously been detected in temperature curves based on planktic foraminifera in the same core, indicating that Radiolaria may be a more sensitive temperature indicator in this region.